Membranous nephropathy in the kidney allograft. Issue 11 (13th October 2016) - Filippone, Edward J.; Farber, John L.
Abstract: Membranous nephropathy (MN) may occur in a kidney transplant as recurrence of the original disease (rMN) or as a de novo MN (dnMN). rMN often occurs early, within the first year, and often in a mild or subclinical fashion. Recurrence cannot be predicted by clinical features at the time of transplantation. The natural history is increasing proteinuria over time, with less chance for spontaneous remission compared to primary MN (pMN). Antiphospholipase A2 receptor (PLA2R) antibodies should be evaluated in all patients with pMN at the time of transplantation and serially. If titers persist or rise, biopsy is indicated. Irrespective of PLA2R status, any case with proteinuria reaching 1 g/day should be biopsied. No randomized controlled trials have been published regarding treatment of rMN. Observational data support use of rituximab. Given the progressive nature of rMN and lack of spontaneous remissions, a period of observation does not seem justifiable. dnMN occurs with about equal frequency as rMN and shares features of secondary MN in native kidneys. Causes include viral infections (e.g., hepatitis B or C), which should be treated. In some cases, dnMN may represent an atypical alloimmune response. The role of rituximab in dnMN is undefined.